Mengintegrasikan Keterampilan Hidup dan Kewirausahaan: Model Pendidikan Alternatif untuk Generasi Muda - Yurlina Ndruru; Indri Purnama Putri Harefa; Yosia Belo (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Globalization has changed the perspective on education, shifting the focus from the conventional face-to-face model to a more open and flexible approach, often referred to as "knowledge age" or 21st-century education. In today's information era, physical distance no longer hinders interactions between individuals and institutions, creating the concept of a "global village." This change is driven by advances in technology and science, which also influence views on education as well as the roles of parents, teachers, and lecturers. Entrepreneurial education has become crucial to prepare students with digital literacy and the skills required in an increasingly interconnected global market. Entrepreneurial readiness can be enhanced through education that focuses on entrepreneurship aspects, including the development of entrepreneurial skills and attitudes. Education functions not only as a means of transferring knowledge but also as a platform for developing critical thinking and life skills, which are essential for facing challenges in the globalization era. Therefore, the integration of technology in education is vital to improve the quality and accessibility of learning worldwide.